The Impact of Self-Efficacy and Teaching Innovation on Teacher Performance - Ashlan, Said; Fajri, Rahmat (Journal of Pedagogy and Education Science, 2025)
This study investigates the influence of teachers’ self-efficacy and teaching innovation on their professional performance. Employing a quantitative research design, the study involved 298 madrasah teachers selected through proportional random sampling. Data were analyzed using path analysis, preceded by the computation of inter-variable correlations presented in matrix form. The analysis reveals that self-efficacy exerts a positive effect on teacher performance, with a standardized coefficient of 0.121, while teaching innovation demonstrates a stronger positive influence, with a coefficient of 0.177. These findings indicate that self-efficacy contributes to a 12.1% enhancement in teacher performance, whereas teaching innovation contributes to a 17.7% improvement. The results underscore the pivotal role of both self-efficacy and innovative teaching practices in enhancing the effectiveness and performance of madrasah teachers.